2008
DOI: 10.1016/j.ejon.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for involvement in treatment decision making of patients with cancer: A review of the literature

Abstract: SummaryA systematic review of the literature about patients' preferences for involvement in cancer treatment decision making was conducted. Establishing preferences is important if the aim is to make health care more sensitive to the needs and expectations of each individual patient. Thirty-one papers were included in the review. Generalising from this literature is problematic because of limitations related to sample size, sample composition and methods used to assess preferences. Whilst we take cognizance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 45 publications
11
114
2
2
Order By: Relevance
“…A cross-sectional study of haematological patients in Australia showed that 44% experienced a mismatch between preferred and perceived degree of participation; of those, 34% had been less involved than they desired [16] . These results correspond to findings in two reviews concluding that patients want more participation than they had actually experienced [17,18] . Yet, we found a higher proportion of patients experiencing a mismatch and furthermore that this mismatch was a result of being involved to a higher degree than desired.…”
Section: Discussion Of Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…A cross-sectional study of haematological patients in Australia showed that 44% experienced a mismatch between preferred and perceived degree of participation; of those, 34% had been less involved than they desired [16] . These results correspond to findings in two reviews concluding that patients want more participation than they had actually experienced [17,18] . Yet, we found a higher proportion of patients experiencing a mismatch and furthermore that this mismatch was a result of being involved to a higher degree than desired.…”
Section: Discussion Of Resultssupporting
confidence: 71%
“…According to Hubbard et al, younger patients tend to prefer more involvement than older patients although no association between health status and role preferences can be claimed to exist [17] . The slight underrepresentation of young patients in our study may thus have contributed to the finding that the majority of respondents preferred staff to make the decisions.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Consistent with findings from other studies [40][41][42] almost two-thirds of women in this study preferred an active role (collaborative or patient-based) in treatment decision-making. Women who are involved in decision-making at a level that is consistent with or greater than their preferred role have better overall decision related outcomes [43] .…”
Section: Issn 2324-7940 E-issn 2324-7959supporting
confidence: 82%
“…Participants recognised that, independent of multimorbidity, age brings greater expectations of health care, 24 but that societal views can influence preferences for shared decision making. 55 The particular influence of other factors on associations between patients' trust is highlighted, and the facilitation of shared decision making, with respect to older patients and the GP. Continuity of care, 56,57 and patient choice for a GP-patient 'match', 51,58 have been associated with patients' trust.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%